Postoperative Cognitive Dysfunction in Craniotomy: Mechanisms, Challenges, and Future Directions - Suandika, Made; Yantoro , Awal Tunis; Suhendro , Anton; Wijayanti, Indri; Handayani, Rahmaya Nova; Yulianto, Dwi Agus; Kisdyanti, Yuniar Melissa (Java Nursing Journal, 2025)
Postoperative cognitive dysfunction (POCD) is a clinical concern that can affect patients undergoing craniotomy, often impairing memory, attention, and executive function. Despite advances in neurosurgical and anesthetic techniques, POCD remains prevalent and under-recognized. This review aims to explore the underlying mechanisms and contributing factors of POCD in the context of craniotomy under general anesthesia. A narrative literature review method was employed to examine publications retrieved from major databases including PubMed, Scopus, and ScienceDirect between 2015 and 2025. Selected studies focused on adult patients and provided insights into both clinical manifestations and molecular pathways linked to POCD. The analysis revealed that factors such as advanced age, duration of anesthesia, and neuroinflammatory responses significantly influence the development of POCD. Mitochondrial dysfunction and oxidative stress were frequently cited as key contributors to neuronal damage following surgery. In terms of clinical management, the literature suggests that early cognitive assessment and tailored anesthetic strategies may reduce the risk of long-term impairment. Although definitive treatment remains elusive, this review highlights the importance of early identification and multidisciplinary approaches to mitigate POCD in post-craniotomy patients. Future research should prioritize standardized diagnostic criteria and explore neuroprotective interventions to improve cognitive outcomes following neurosurgical procedures.